Ijtihad Tathbiqi dan Kontribusinya dalam Pengembangan Ekonomi Syariah - Adhe Pertiwi Mareta; Syamsul Hilal; Moh. Bahrudin (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
In the context of Islamic economics, many contemporary issues are not explicitly regulated by Islamic legal sources, thus requiring ijtihad to adapt the law to current circumstances. Ijtihad Tathbiqi is defined as the effort to apply established sharia laws in the specific context of daily life. This research aims to explain the concept of ijtihad tathbiqi, the legal requirements for a mujtahid, the objects of ijtihad tathbiqi, the implementation steps, as well as its potential and contribution to the development of the sharia economy in Indonesia.